Peningkatan Kemampuan Siswa Memahami Puisi dengan Model Strata Norma - Nurhayati Nurhayati (Jurnal Ilmu Pendidikan, 2016)
The purpose of the research is to increase the student comprehension on poetry so that the students can understand poems they read. A norm strata model is used. This model considers poetry to comprise several strata (layers) of norms. Each norm brings about layers below it. The process consists of three cycles. Based on the determined criteria of success it shows that the cycle I is not yet successful. 57% of the students score 6.5. At cycle II 93% score 6.5. At cycle III, students understand the poetry being taught. However, the final test score drops when compared to the average test score of cycle II. The results from the final test questions given at cycle III are different from those at cycle II which are familiar to the students. Yet, cycle III meets the criteria of success because 89% of the students score 6.5